2009
DOI: 10.1021/jf9005033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat on Aspalathin, Iso-orientin, and Orientin Contents and Color of Fermented Rooibos (Aspalathus linearis) Iced Tea

Abstract: The phenolic quality of commercial South African fermented rooibos iced teas in terms of aspalathin, iso-orientin, and orientin contents in comparison to a "cup of tea" was shown to be inferior. The role of the different manufacturing stages of powdered extract used in iced tea formulation and, more specifically, the impact of pasteurization and sterilization on the color and phenolic content of the beverage, were assessed as potential causes of its inferior phenolic quality. Aspalathin and its corresponding f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 16 publications
1
32
0
Order By: Relevance
“…Rooibos has been shown to prevent chemically induced liver damage [77], inflammation [78], lipid oxidation [79], hyperglycemia [80], and oxidative stress [81]. These antioxidant effects of Rooibos tea may be related to the presence of antioxidant polyphenol compounds, including aspalathin (dihydrochalcone C-glucoside aspalathin), nothofagin (C–C linked dihydrochalcone glucoside), and other flavonoids (isoorientin and orientin, which are both oxidation products of aspalathin that are characterized by higher stability at high temperatures and under varying pH conditions) [82]. While we have confirmed that drinking Rooibos tea protects against oxidative effects induced by immobilization stress in rats, the exact mechanism of action of Rooibos is still largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Rooibos has been shown to prevent chemically induced liver damage [77], inflammation [78], lipid oxidation [79], hyperglycemia [80], and oxidative stress [81]. These antioxidant effects of Rooibos tea may be related to the presence of antioxidant polyphenol compounds, including aspalathin (dihydrochalcone C-glucoside aspalathin), nothofagin (C–C linked dihydrochalcone glucoside), and other flavonoids (isoorientin and orientin, which are both oxidation products of aspalathin that are characterized by higher stability at high temperatures and under varying pH conditions) [82]. While we have confirmed that drinking Rooibos tea protects against oxidative effects induced by immobilization stress in rats, the exact mechanism of action of Rooibos is still largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of aspalathin, nothofagin, isoorientin and orientin was performed in duplicate by HPLC with diode-array detection as previously described by Joubert et al (2009) on an Agilent 1200 system (Agilent, Santa Clara, CA, USA). Calibration curves were prepared using five concentrations of aspalathin, nothofagin, isoorientin and orientin from 0.01 to 2 mg per injection.…”
Section: Quantification Of Individual Flavonoidsmentioning
confidence: 99%
“…The monomeric flavonoid composition of rooibos is unique in that it contains the novel dihydrochalcone C ‐glycoside, aspalathin , as well as the cyclic dihydrochalcone, aspalalinin . Rooibos tea furthermore represents an important dietary source of the C ‐glycosyl flavones, such as orientin and isoorientin , both major phenolic constituents of fermented rooibos infusions and extracts . In order to exploit the full potential of rooibos as phytopharmaceutical and to realise authentication of rooibos extracts, comprehensive data regarding its phenolic composition are required.…”
Section: Introductionmentioning
confidence: 99%